Employing a Quality Improvement Database to Observe the Gaps in Care at a Student-Run Free Clinic - Grimmond, Jessica; Menning, Melanie (Journal of Student-Run Clinics, 2022)
The Student Health Alliance Reaching Indigent Needy Groups (SHARING) clinics are student run free clinics (SRFCs) at the University of Nebraska Medical Center that serve low income, uninsured adults in Omaha, Nebraska. Like many other SRFCs, they face multiple barriers to providing high quality care. To address this, the SHARING Quality Improvement (QI) Database was created. QI has many definitions, but, overall, it is a method of analyzing clinic performance and the changes made to improve the clinic. Before this database, there was no way of continuously tracking clinic metrics over time, so previous QI projects required timely data abstraction that often only evaluated retrospective outcomes with limited real-time data to track clinical outcomes as changes were implemented thereby limiting our ability to implement further changes to improve patient health. A review of SRFC literature reveals a lack of a model or guide on how to assess quality of care in SRFCs and track patient data over time. This study seeks to fill this gap. Our database consists of a patient list of electronic medical records that were compiled in the charting system Epic. The patient data is exported into a Microsoft Excel document each month and clinic metrics are analyzed, thus providing a real-time dashboard of quality metrics for the clinic. This database will be utilized to inform decisions regarding the reform of clinic processes. This database model can be used at other SRFCs to monitor quality of care provided at their clinics and implement QI measures accordingly.